2011
DOI: 10.1038/tp.2011.44
|View full text |Cite
|
Sign up to set email alerts
|

Differential susceptibility in youth: evidence that 5-HTTLPR x positive parenting is associated with positive affect ‘for better and worse’

Abstract: Positive affect has been implicated in the phenomenological experience of various psychiatric disorders, vulnerability to develop psychopathology and overall socio-emotional functioning. However, developmental influences that may contribute to positive affect have been understudied. Here, we studied youths' 5-HTTLPR genotype and rearing environment (degree of positive and supportive parenting) to investigate the differential susceptibility hypothesis (DSH) that youth carrying short alleles of 5-HTTLPR would be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
108
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(119 citation statements)
references
References 63 publications
(92 reference statements)
10
108
1
Order By: Relevance
“…Although the autoregressive parameters in the model account for the influence of preexisting depression that may have been influenced by genetic and environmental factors that may have been set in motion in early childhood, it does not necessarily account for ongoing interaction of genetic vulnerability and environmental factors. Related lines of research have found support for specific cognitive processes, such as rumination (Flancbaum, et al, 2011) and depressive inferential styles (Abela, Skitch, Adams, & Hankin, 2006; Abela, et al, 2009), as well gene x environment interactions (Hankin, et al, 2011) that may account for the associations between maternal and offspring depression.…”
Section: Discussionmentioning
confidence: 99%
“…Although the autoregressive parameters in the model account for the influence of preexisting depression that may have been influenced by genetic and environmental factors that may have been set in motion in early childhood, it does not necessarily account for ongoing interaction of genetic vulnerability and environmental factors. Related lines of research have found support for specific cognitive processes, such as rumination (Flancbaum, et al, 2011) and depressive inferential styles (Abela, Skitch, Adams, & Hankin, 2006; Abela, et al, 2009), as well gene x environment interactions (Hankin, et al, 2011) that may account for the associations between maternal and offspring depression.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of work suggests that S allele carriers, while more sensitive to stress, may also be more responsive to supportive environments or treatment interventions to reduce the impact of environmental stressors (Kaufman et al, 2004, Hankin et al, 2011). It has been hypothesized that the S allele is a “plasticity factor” rather than simply a risk factor following exposure to adverse environment (e.g., Kuepper et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The link between high stress and depression appears to be further exacerbated in people who carry a short allele in the serotonin transporter polymorphism (5-HTTLPR, linked to serotonin function) (Caspi, Hariri, Holmes, Uher, & Moffitt, 2010; Caspi et al, 2003; Kim et al, 2007; Lesch et al, 1996; Manuck & McCaffery, 2014; Uher & McGuffin, 2010), a group that represents approximately 40–70% of the general population (Kim et al, 2007). These individuals – compared to those without a short allele – appear to be particularly sensitive to the quality of their environment, such that experiencing negative environments is associated with significantly worse psychological health (Belsky & Pluess, 2009; Hankin et al, 2011; Taylor et al, 2006). Given that genes and stressful environments are not always modifiable, how can people with this risky combination avoid depression?…”
mentioning
confidence: 99%